Manual de procedimientos para la mejora en la gestión del Hotel Laboratorio Higuerón de la ESPAM MFL - Marcillo Mera, Miguel Andrés (2022)
The objective of the research is to design a manual of procedures for the improvement in the management of the Hotel Laboratory Higuerón of the ESPAM MFL, the information collected was obtained through bibliographic review and field work, being an exploratory-descriptive process. Regarding the results, in the first phase through a diagnosis, the main characteristics of the establishment were identified, corresponding to mission, vision, structure, institutional objectives and main services. In the second phase, the evaluation of the processes and sub-processes was made, applying tools such as the interview, internal analysis, the evaluation of processes, through the ISOS/IEC 15504 model, where the main existing problems were identified, in addition to graphing the main procedures that the institution executes, demonstrating each one of the activities that are developed in the work areas. As a last phase, the procedures manual was prepared, definition and analysis of the information, design and structure of the manual, and main objective, where all the procedures to be followed in each area or department were defined, based on the standards hotel management quality standards aligned with INEN standards. In conclusion, the procedures manual was developed, allowing the organization of activities and processes in the different operational and administrative areas of the Laboratory Higuerón hotel of ESPAM MFL.